Oxidative RNA Modifications as an Early Response of Soybean (Glycine max L.) Exposed to Copper and Lead - Chmielowska-Bąk, Jagna; Shcheglova, Ekaterina; Rosik, Konrad; Yushin, Nikita; Zinicovscaia, Inga; Deckert, Joanna (Frontiers in Plant Science, 2022)
Plant exposure to metals is associated with the accumulation of reactive oxygen species, which mediate the oxidation of various molecules including lipids, proteins, and nucleic acids. The aim of the present study is the evaluation of the impact of short-term Cu and Pb treatment on oxidative events in the roots of soybean seedlings, with special emphasis on RNA oxidation. The results show that an increase in total RNA oxidative modification, 8-hydroxyguanosine (8-OHG), constitutes a very early response to both applied metals, observed already within the first hour of treatment. Exposure to Cu and Pb resulted also in the increase in superoxide anion and hydrogen peroxide levels and intensified lipid peroxidation. However, these responses were most prominent after longer treatment times. On the other hand, no changes were observed in the level of protein carbonylation. It can be concluded that 8-OHG enrichment in total RNA constitutes one of the earliest reactions to metals, which precedes the symptoms of oxidative stress.